Analisis Trend (Indeks Number Trend Series Analysis) PT. Adaro Energi Indonesia Tbk - Putri, Afrianti Kartika (BISMA : Business and Management Journal, 2024)
PT Adaro Energy Indonesia (ADRO) is one of the leading coal companies in Indonesia. Trend analysis of the company's number trend series index is important to understand the pattern and direction of its performance movement over a certain period of time. This research aims to analyze the trend of the ADRO number trend series index using linear and exponential regression methods. The data used in this research is ADRO Financial Report data for the period 2020 to 2023. The results of the analysis show that the overall ADRO number trend series index trend has increased. Linear and exponential regression models show quite good results in explaining data trends. Trend analysis (Index Number Trend Series Analysis) is carried out by comparing financial reports for the last 5 years. In the index-number trend series analysis approach, comparisons are made by calculating the relative change (percentage) of each element of the financial report over several years based on a certain base year. Usually what is designated as the base year is the earliest year (period) of a series of financial report periods being analyzed. . However, the main consideration in determining the base year is the financial reporting period that shows the most normal conditions.